Outcomes of patients diagnosed with COVID-19 in the early postoperative period following cardiac surgery. (13th August 2020) - Yates, Martin T; Balmforth, Damian; Lopez-Marco, Ana; Uppal, Rakesh; Oo, Aung Y
Abstract: The coronavirus 2019 (COVID-19) pandemic has disrupted patient care across the NHS. Following the suspension of elective surgery, priority was placed in providing urgent and emergency surgery for patients with no alternative treatment. We aim to assess the outcomes of patients undergoing cardiac surgery who have COVID-19 infection diagnosed in the early postoperative period. We identified 9 patients who developed COVID-19 infection following cardiac surgery. These patients had a significant length of hospital stay and extremely poor outcomes with mortality of 44%. In conclusion, the outcome of cardiac surgical patients who contracted COVID-19 infection perioperatively is extremely poor. In order to offer cardiac surgery, units must implement rigorous protocols aimed at maintaining a COVID-19 protective environment to minimize additional life-threatening complications related to this virus infection. Abstract : The coronavirus 2019 (COVID-19) pandemic has disrupted patient care across the NHS.